The Unsung Heroines of India’s Freedom Struggle - Ganie, Zahied Rehman; Sisodia, Shanti Dev (American International Journal of Social Science Research, 2020)
The history of Indian Freedom Struggle would be incomplete without mentioning the contribution of women. The sacrifice made by the women of India will occupy the foremost place. They fought with true spirit and undaunted courage and faced various tortures, exploitations and hardships to earn us freedom. When most of the men freedom fighters were in prison the women came forward and took charge of the struggle. The list of great women whose names have gone down in history for their dedication and undying devotion to the service of India is a long one. Woman’s participation in India’s freedom struggle began as early as in1817. Bhima Bai Holkar fought bravely against the British colonel Malcolm and defeated him in guerilla warfare. Many women including Rani Channama of Kittur, Rani Begum Hazrat Mahal of Avadh fought against British East India company in the 19th century; 30 years before the “First War of Independence 1857” The role played by women in the War of Independence (the Great Revolt) of 1857 was creditable and invited the admiration even leaders of the Revolt. Rani of Ramgarh, Rani Jindan Kaur, Rani Tace Bai, Baiza Bai, Chauhan Rani, Tapasvini Maharani daringly led their troops into the battlefield. Rani Lakshmi Bai of Jhansi whose heroism and superb leadership laid an outstanding example of real patriotism .Indian women who joined the national movement belonged to educated and liberal families, as well as those from the rural areas and from all walk of life, all castes, religions and communities. Sarojini Naidu, Kasturba Gandhi, Vijayalakmi Pundit and Annie Besant in the 20th century are the names which are remembered even today for their singular contribution both in battlefield and in political field.